Disclosing the Biocide Activity of α-Ag2−2xCuxWO4 (0 ≤ x ≤ 0.16) Solid Solutions - Pereira, Paula Fabiana dos Santos; De Foggi, Camila Cristina; Gouveia, Amanda Fernandes; Pinatti, Ivo Mateus; Cabral, Luís Antônio; Guillamon, Eva; Sorribes, Iván; San-Miguel, Miguel A.; Vergani, Carlos Eduardo [UNESP]; Simões, Alexandre Zirpoli [UNESP]; da Silva, Edison Z.; Cavalcante, Laécio Santos; et al. (MDPI, 2022)
In this work, α-Ag2−2xCuxWO4 (0 ≤ x ≤ 0.16) solid solutions with enhanced antibacterial (against methicillin-resistant Staphylococcus aureus) and antifungal (against Candida albicans) activities are reported. A plethora of techniques (X-ray diffraction with Rietveld refinements, inductively coupled plasma atomic emission spectrometry, micro-Raman spectroscopy, attenuated total reflectance–Fourier transform infrared spectroscopy, field emission scanning electron microscopy, ultraviolet–visible spectroscopy, photoluminescence emissions, and X-ray photoelectron spectroscopy) were employed to characterize the as-synthetized samples and determine the local coordination geometry of Cu2+ cations at the orthorhombic lattice. To find a correlation between morphology and biocide activity, the experimental results were sustained by first-principles calculations at the density functional theory level to decipher the cluster coordinations and electronic properties of the exposed surfaces. Based on the analysis of the under-coordinated Ag and Cu clusters at the (010) and (101) exposed surfaces, we propose a mechanism to explain the biocide activity of these solid solutions.
Keywords: biocide activity; DFT study; morphology; α-Ag2−2xCuxWO4 solid solutions